(untitled) (Journal of the College of Education for Women, 2019)
Through the above-mentioned evidence and opinions on this literary term of art which was not an emergency event or a term recently invented . But its roots stands since ancient times, especially in the unit of independent poetic system , or united poetic unit in the poem, where unit including the densest words and a broader meaning or significance which has been referred to in the midst of this research and the final result that we have reached is that the term condensation can be classified in the equation ofa new literarylistas follows:Case Pressure Emotionalliteracy andflowingof article + Rich Economy of language in terms ofsymboland image = Heavy wordin a broad sense.As well as enable the poet to his language and his intelligence with the fast intuitive which shred the poets of the Abbasid period , and that form they have as a phenomenon of art earned them a feature of immortality and poetic creativity throughout the ages by employing the term condensation in the introductions to poems , which dominates the rest of the verses or overshadow the poem itself, which was the motive of our ancient critics to establish a balance between different poets through the condensation which reveals at the same time a unique talent and artistic tastewithout the need forelaboration ordetail , butenough fora snapshotoroverview of a unique or imaginative owned by the poet and leads him to step up and summarize what they see from the experiences and descriptions of the sights and reflected its beauty through condensation which reveals the talents and unique of the poets and the gift. and to renew what is familiar and display it in the broadest sense and outlined theword, whichdisclosedthe termcapillarycondensation.